Live Better Electrically with Message from the Sun - Avtar Singh Gill (Fundamental Research and Application of Physical Science Vol. 9, 2023)
Aim: The aim of this study is to explain how to multiply the mild Solar electrical energy for use on planet Earth. ‘Live Better Electrically’ is a component of my ‘Message from the SUN’ article and explains the use with amplification of the mild Solar electrical energy in micro-amperes or low milli-amperes reaching the Earth with the ‘Coil Effect’. The Northern and Southern Lights are caused by the Solar IMF1. ‘Gill’s Electronic Theory of Magnetism 1964’ shows how the solar IMF on approaching the magnetosphere of the Earth splits into its negative and positive electric energy components which head for the opposite magnetic poles of the Earth to cause the equally bright Aurora Borealis and Aurora Australis. Some applications to harness this solar electrical energy reaching the Earth are presented and dot product equations are presented to support these applications without any need of Henrik Lorentz’s 1893 cross products. Line diagrams will explain how to amplify the mild solar electrical energy reaching the Earth as required. ‘Gill’s electronic theory of magnetism 1964’ explains better and should replace ‘Maxwell’s dipole theory of magnetism 1873’.